Occurrence of snow leopard Panthera uncia (Scherber, 1775) in the territory of the Katon-Karagai National Park (South-West Altai, East Kazakhstan) - A.U. Gabdullina; Zh.B. Amanbaev (Acta Biologica Sibirica, 2019)
The note provides information on the new meeting of the snow leopard Panthera  uncia (Scherber, 1775) on the territory of the Katon-Karagai National Park (South-West Altai, East Kazakhstan). This rare mammal species listed in the Red Data Book of the Republic of Kazakhstan and the Red List of the International Union for Conservation of Nature (IUCN)